Radiation-free diagnosis of scoliosis: An overview of the surface and spine topography Strahlenfreie Diagnostik bei Skoliosen: Ein Überblick über die Oberflächen- und Wirbelsäulentopographie - Wild, M.; Rath, B.; Tingart, M.; Schulze, A.; Quack, V.; Betsch, Marcel (Orthopäde, 2015)
Background: Scoliosis is a complex three-dimensional deformity of the spine, which usually occurs during childhood and adolescence. Up to now, whole spine X-rays have been the therapeutic gold standard in the diagnosis and follow-up of scoliosis. Aim: This review gives a brief overview of the history, technical background and possible fields of use for video-rasterstereography Methods: Alternative measurement systems have been developed over the past few years for the treatment of scoliosis, because of the risk of radiation exposure of X-rays. The rasterstereographic system Formetric (Diers International GmbH, Schlagenbad) allows a radiation-free, three-dimensional analysis of the back surface and the spine. Outlook: Even dynamic measurements can now be conducted with this rasterstereographic system, which will help to further understand and analyze the human spine.
CRIS-Team Scopus Importer:2022-07-20
Keywords: Posture; Spinal curvatures; Spine; Stereophotogrammetry; Three-dimensional imaging